2020
DOI: 10.1017/s1368980020005248
|View full text |Cite
|
Sign up to set email alerts
|

Social media analytics in nutrition research: a rapid review of current usage in investigation of dietary behaviours

Abstract: Objective: Social media analytics (SMA) has a track record in business research. The utilisation in nutrition research is unknown, despite social media being populated with real-time eating behaviours. This rapid review aimed to explore the use of SMA in nutrition research with the investigation of dietary behaviours. Design: The review was conducted according to rapid review guidelines by WHO and the National Collaborating Centre for Methods and Tools. Five databases of peer-reviewed, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 78 publications
(7 reference statements)
0
9
0
Order By: Relevance
“…There have been other scoping reviews undertaken to investigate studies using social media analysis in the field of health research more broadly 45–47 and one focusing on 34 nutrition studies was identified 25 . Of the 79 studies in the current review, only 11 overlap, which may be attributed to differences in search strategies.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…There have been other scoping reviews undertaken to investigate studies using social media analysis in the field of health research more broadly 45–47 and one focusing on 34 nutrition studies was identified 25 . Of the 79 studies in the current review, only 11 overlap, which may be attributed to differences in search strategies.…”
Section: Discussionmentioning
confidence: 97%
“…Of the 79 studies in the current review, only 11 overlap, which may be attributed to differences in search strategies. Twenty‐one of the studies included here were published after the date of the other review's 25 search of databases (2020–2021). Nevertheless, commonalities were observed, including the finding that Twitter data was most commonly used, few were from the nutrition discipline and most studies were from the USA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…#veganuary was used as an example to showcase the advantages of this new research area for studying emerging and spreading food trends. Given the importance of food consumption in the grand scheme of climate change, impact on the environment and health behaviour, consumer research must focus on dietary and health trends (Stirling et al, 2021). • Provides complementary insights for consumer studies when applied together with standard quantitative and qualitative tools.…”
Section: Discussionmentioning
confidence: 99%
“…#veganuary was used as an example to showcase the advantages of this new research area for studying emerging and spreading food trends. Given the importance of food consumption in the grand scheme of climate change, impact on the environment and health behaviour, consumer research must focus on dietary and health trends (Stirling et al ., 2021). Below we recap the advantages of Social Media Analytics and pose open questions for future research: Provides complementary insights for consumer studies when applied together with standard quantitative and qualitative tools. Allows detection of new trends and topics. Enables display of relationships between food trends and influencers. Can be used by producers to specifically design their products towards (niche) consumers. Can be used by policymakers to immediately identify how public health measures in the food space are working. Generates economies of scale in data collection: Big datasets are available to do research in a comparatively short amount of time. …”
Section: Discussionmentioning
confidence: 99%